2017
DOI: 10.1016/j.jnnfm.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A dissipative particle dynamics model for thixotropic materials exhibiting pseudo-yield stress behaviour

Abstract: Many materials (e.g., gels, colloids, concentrated cohesive sediments, etc.) exhibit a stable solid form at rest, and liquify once subjected to an applied stress exceeding a critical value -a yield-stress behaviour. This can be qualitatively explained by the forming and destruction of the fluid microstructure [1], and it may be modelled as a thixotropic and yield stress material. In this paper, we propose a mesoscopic model which is able to mimic a thixotropic and yield stress behaviour using a particle-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Few studies have been carried out to calculate shear stress using molecular models. Recently, Le-Cao et al (2017) developed a model to calculate shear properties of a fluid by utilizing DPD method. They divided DPD particles into two categories by applying the indirect linkage dissipative particle (ILDP) model.…”
Section: Investigation Of Shearing Properties Of Mr Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have been carried out to calculate shear stress using molecular models. Recently, Le-Cao et al (2017) developed a model to calculate shear properties of a fluid by utilizing DPD method. They divided DPD particles into two categories by applying the indirect linkage dissipative particle (ILDP) model.…”
Section: Investigation Of Shearing Properties Of Mr Fluidmentioning
confidence: 99%
“…Also, they defined particular weight functions and calculated exerted force by particles so that shear stress can be computed by utilizing this force. Further details on their study can be found in the study by Le-Cao et al (2017).…”
Section: Investigation Of Shearing Properties Of Mr Fluidmentioning
confidence: 99%
“…In fact, new forces (elastic, rigid, etc.) can be added between particles in order to describe long polymers [71][72][73][74] , rigid or deformable particles in suspension [75] , porous media [76] , droplets [77] , cells [78][79][80] , or even more complex thixotropic materials [81] (see Fig. 1).…”
Section: How Is the Fluid Complexity Incorporated In Sdpd?mentioning
confidence: 99%
“…DPD conserves momentum locally and therefore preserves hydrodynamics. The method has been used to simulate various fluid systems, for example, particulate suspensions [5,6,7], microfluidic systems [8], red blood cells [9], thixotropic materials [10], polymer solutions [11], nanoporous shales [12], to name a few. In DPD, the solvent phase is simply modelled by a set of particles (called DPD particles) under their Newton second law motions, while the suspended phases (e.g., solid particles, droplets, bubbles and polymer chains) can all be constructed from the DPD particles through appropriate constraints.…”
Section: Introductionmentioning
confidence: 99%